Support for nurses directly involved with women who chose to terminate a pregnancy - AC Gmeiner; S Van Wyk; M Poggenpoel; CPH Myburgh (Curationis, 2000)
Research conducted by Poggenpoel, Myburgh and Gmeiner (1998:2-8) on “One voice regarding the legalization of abortion: Nurses who experience discomfort” indicated that the nurses were in favour of the fact that nurses should volunteer to participate in terminating a pregnancy of a woman. From our observations in clinics where nurses voluntarily participate in providing reproductive health services, including termination of pregnancy, it became clear that supporting these nurses may be essential. To be able to provide support, it is necessary to identify, explore and describe nurses’ experience of being directly involved with women who terminate their pregnancy. To enable us to address the identified problems, a qualitative research strategy was implemented in which respondents were included in the sample through purposive sampling. Phenomenological interviews were conducted individually. Data was analysed by means of Tesch’s descriptive approach. Thereafter, guidelines for operationalisation were inferred from the results and a literature control completed to verify and enrich guidelines. Measures to ensure trustworthiness have been applied in the research and ethical measures have been strictly adhered to regarding this sensitive issue.